Dialogical Selves: Exploring “Sameness and Difference” in “Queer” Identification - Phillips, Tyler (Department of Psychology, 2023)
“The LGBTQIA+ community”, like all social groupings, is moulded by dialectical forces: inclusivity/exclusivity, belonging/non-belonging, sameness/difference. Literature on it is riddled with dichotomous conflicts over (dis)identification and (anti)relationality in theory, lived experiences, and political mobilisation. Dominant discourses tend to overlook intersectional complexities therein, focus on labels over interactions, and reiterate a framing of the LGBTQIA+ as inherently vulnerable. The gaps point to a need for a more open and reparative investigation that creates space for exploring and (re)negotiating the assumed coalition. This study investigated what diverse groups of queer-identified individuals experienced when sharing their lived accounts of “sameness and difference” with others. Twenty-one people each participated in one of four focus groups and in a follow-up interview were invited to reflect on their experience. Decolonial Intersectional Narrative Analysis (Boonzaier, 2019) and a Bakhtinian-dialogical analysis (Grossen & Salazar Orvig, 2011) were used to inspect the “what” and the “how” of the group dialogues, respectively. Participants recounted significant experiences of sameness and difference that both foregrounded and transcended their particular intersectional identities. Moments/relationships of being treated as more an object than a full subject, due to divergence from certain monoglossic gendered/sexed/sexual norms (both intra- and extra-communally), were conarrated as keys to ongoing queer abjection. Participants expressed that dialoguing in this particular setting was an experience of coming-out-of-isolation, intersubjective learning, and strengthening senses of self and community. Future research and activism are encouraged to invest in accessible open dialogue as a site itself for LGBTQIA+ community-building in South Africa and beyond.